Prevalence and risk factors for soil-transmitted helminth infection in mothers and their infants in Butajira, Ethiopia: a population based study - Alem Atalay; Hanlon Charlotte; Erko Berhanu; Amberbir Alemayehu; Medhin Girmay; Belyhun Yeshambel; Venn Andrea; Britton John; Davey Gail (BMC, 2010)
Abstract Background Soil-transmitted helminths (STHs) are widespread in underdeveloped countries. In Ethiopia, the prevalence and distribution of helminth infection varies by place and with age. We therefore investigated the prevalence of and risk factors for STH infection in mothers and their one year-old children living in Butajira town and surrounding rural areas in southern Ethiopia. Methods In 2005-2006, 1065 pregnant women were recruited in their third trimester of pregnancy. In 2006-2007, when children reached their first birthdays, data on the infants and their mothers were collected, including stool samples for qualitative STH analysis. Questionnaire data on various demographic, housing and lifestyle variables were available. Logistic regression analysis was employed to determine the independent risk factors for STH infection in the mothers and children. Results 908 mothers and 905 infants provided complete data for analysis. Prevalence of any STH infection was 43.5% (95% confidence interval (CI) 40.2-46.8%) in mothers and 4.9% (95%CI 3.6-6.5%) in children. In the fully adjusted regression model, infrequent use of soap by the mother was associated with increased risk (odds ratio (OR) 1.40, 95% CI 1.04-1.88, and 1.66, 95% CI 0.92-2.99, for use at least once a week and less frequent than once a week respectively, relative to daily use; p for trend = 0.018), and urban place of residence (OR 0.45, 95% CI 0.28-0.73, p = 0.001) was associated with reduced risk of maternal STH infection. The only factor associated with STH infection in infants was household source of water, with the greatest risk in those using piped water inside the compound (OR 0.09, 95% CI 0.02-0.38 for river water, 0.20, 95% CI 0.56-0.69 for either well or stream water and 0.21, 95% CI 0.09-0.51 for piped water outside compared with piped water inside the compound, overall p = 0.002) Conclusion In this rural Ethiopian community with a relatively high prevalence of STH infection, we found a reduced risk of infection in relation to maternal hygiene and urban living. Daily use of soap and a safe supply of water are likely to reduce the risk of STH infection.